Clinical severity of RSV bronchiolitis. Issue 2 (22nd March 2022) - Hussain, Faris; Delgado Thompson, Margarita; Vick, David; West, Jack; Edwards, Martin
Abstract: Background: Studies comparing the severity of respiratory syncytial virus (RSV) bronchiolitis to other viruses are inconclusive. Our study aimed to compare the severity of bronchiolitis according to the virus. Methods: Data were collected from 1152 infants under one year of age admitted to Children's hospital for Wales, over the winter months of 2014–2020. The cohort was divided based on the virus detected: RSV, RSV with another virus, or other virus. Using t tests and Fisher exact statistical test, the groups were compared based on length of hospital stay, admissions PICU/HDU, intubations, and need of nasogastric (NG) nutritional support. Results: Fifty‐six percent throat swabs were RSV positive, 15% had RSV with another virus, and 29% had only another virus. Children positive for RSV had statistically longer hospital admissions and were more likely to need NG nutrition; however, there was no difference between number of PICU/HDU admissions or intubations. The RSV group and RSV with another virus group had no statistical differences.